Alternative traffic signal prediction model - Chang, Alicia Yun Lin (Nanyang Technological University, 2021)
In this paper, an alternate version of traffic model is proposed to measure the same related work to track and detect transition time based on vehicle’s displacement from the starting point. The research problem is to find a more efficient and/or a more accurate method to measure the small traffic signal transition time. The experimental data will be collected in Singapore, one intersection during the peak hours. This report aims to test an alternative variable method of the same studies done by Mr Luo Rui Kang on traffic signal prediction to get similar or close to results from his paper. In the final analysis, the alternative variable used to present the same or similar data for traffic system prediction is the data collected from the distance change with respect to the time change in traffic transition change. An analysis collated will also be presented for this transition.